THE ANALYSIS OF CODE-MIXING FOUND IN PRETTY LITTLE LIARS INDONESIA SERIES - Frederico, Mario Lory; Sulatra, I Komang; Puspita, Komang Dian (LPPM Universitas Dhyana Pura, 2024)
The study is concerned with the phenomenon of mixing two or more languages called code-mixing that are found in the Pretty Little Liars Indonesia Series. This study aims at finding out the types of code mixing and the reason of code mixing found from the conversations of the characters in Pretty Little Liars Indonesia Series. Observation method was used in collecting the data. The method used in analyzing the data was descriptive qualitative method by applying the theory by Hoffman (1991). This result of this research reveals that code mixing occurs when speakers mix two or more languages in one utterance. This study shows that all types of code-mixing are found, such as; intra-sentential code-mixing, intra-lexical code-mixing, and involving a change of pronunciation. Meanwhile, the top three for the reason of code-mixing that were found are talking about particular topic (84.21%). interjection (13.16%), and intention of clarifying the speech content for interlocutor (2.63%). Some of the reasons were not found in the data, namely; quoting someone’s word, expressing feeling about something, repetition used for clarification, and expressing group identity, because in the dialogue the characters never have related to the reason of code-mixing.